Fashion advertising a factor related to the clothing buying preferences of selected female teenagers in Metro Manila - Santos, Ma. Lolita Manalo; Mayo, Adelaida, V. (1997.)
The observation of teenagers' demand for clothing, the competition in the clothing retail market and advertising being an essential element in any present retail environment lead to the study on finding out if fashion advertising is a factor on the clothing buying preferences of teenagers. The study intended to determine the medium of advertising that gives impact to their decision. Questionnaire survey were given out to fifty (50) female high school students of St. Paul's College Pasig. Pertaining questions about buying behavior, influential factors, clothing preferences, frequently encountered median and media preferences which gives impact on their clothing preferences and purchases were analyzed. Results and findings of the study indicated that teenagers choose their clothes and prefer signature brands. They considered friends and family influential, however still, considered media/advertising as a factor to their preferences and purchases. Teenagers encountered and watched television more than any other medium. The findings also showed that the mot encountered is not the most effective. Magazines were the preferred medium of the majority of the teenagers because of its qualty in printing, prestige and most of all, its catering to a specific market.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing and dress--Philippines--Psychological aspects; Advertising--Fashion.